SAURON: integral-field spectroscopy of galaxies - Peletier, R; Davies, R; Allington-Smith, JR; Bacon, R; Copin, Y; Emsellem, E; de Zeeuw, P; Miller, B; Bureau, M; Verolme, E; Carollo, C; Monnet, G (2001)
We present the first results from a new and unique integral-field spectrograph, SAURON, for the 4.2-m William Herschel Telescope on La Palma. Based upon the TIGER concept, SAURON uses a lens array to obtain two-dimensional spectroscopy with complete spatial coverage over a field of 33″×41″ in low-resolution mode (0.94″ lenslets) and of 9″×11″ in high-resolution mode (0.26″ lenslets). The spectra cover 4800 Å to 5400 Å with a resolution of 3 Å (σ=75 km s-1). SAURON achieved first light during commissioning on the WHT on 1 February 1999. The instrument performed well and we are commencing a systematic survey of the velocity dispersions, velocity fields, and line-strength distributions in nearby ellipticals and spiral bulges. The wide field of SAURON will be crucial for unravelling complicated velocity structures. In combination with available long-slit spectroscopy of the outer regions of the galaxies, HST spectra of the nuclei, and HST imaging, we will constrain the intrinsic shapes, mass-to-light ratios, and stellar populations in spheroids. In this presentation we will give a status report and preliminary results from our first science run in February 1999. © Elsevier Science B.V.